Engaging students as partners in global learning : final report. - Green, Wendy (Australia. Dept of Education, 2019)
University ideally prepares graduates who can live, work and continue to learn effectively and ethically in the interconnected, interdependent world of the 21st century. For all graduates, whether they remain in an increasingly pluralist Australia or move abroad, development of these capabilities is vital. This Australian Learning and Teaching Fellowship (ALTF) program addressed this gap by engaging students and staff as partners in the process of global learning. Activities linked students, academic and professional staff, university management and peak national and international associations in order to plan, enact, evaluate and disseminate innovative global learning in the formal and co-curriculum, at home universities and abroad. The program of activities began in January 2017. Initially, the fellowship program was projected to conclude in December 2017 but was extended to December 2018. The first activities focussed on developing and supporting a network of interested Australian academics, professional staff, alumni and students. Analysis of surveys and narrative interviews conducted during the Fellowship highlighted the following four themes: enhanced agency of students and staff, enhanced global learning, motivations, and challenges. [Executive summary, ed]